2007
DOI: 10.1189/jlb.0807586
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of TLR2 with TLR1 or TLR6 expands the ligand spectrum but does not lead to differential signaling

Abstract: TLR are primary triggers of the innate immune system by recognizing various microorganisms through conserved pathogen-associated molecular patterns. TLR2 is the receptor for a functional recognition of bacterial lipopeptides (LP) and is up-regulated during various disorders such as chronic obstructive pulmonary disease and sepsis. This receptor is unique in its ability to form heteromers with TLR1 or TLR6 to mediate intracellular signaling. According to the fatty acid pattern as well as the assembling of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(212 citation statements)
references
References 47 publications
4
196
1
5
Order By: Relevance
“…A similar observation was made using Pam2EQL as a model. Moreover, the engagement of TLR2 led to the activation of multiple signaling pathways in DCs, including JNK, p38, ERK, MyD88, and NF-kB signaling (32,33). Our data showed that the upregulation of Rab7 is dependent on MyD88 pathway (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A similar observation was made using Pam2EQL as a model. Moreover, the engagement of TLR2 led to the activation of multiple signaling pathways in DCs, including JNK, p38, ERK, MyD88, and NF-kB signaling (32,33). Our data showed that the upregulation of Rab7 is dependent on MyD88 pathway (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…4B, 4C). Previous studies showed TLR2 activation resulted in downstream MAPK signaling, such as JNK, p38, and ERK signaling (32,33). To further investigate the signaling pathways of TLR2 that regulate Rab7 expression, MAPK signaling inhibitors were used to treat BMDCs.…”
Section: Tlr2 Facilitates Pam2idg Endocytosis By Bmdcs and Is Requirementioning
confidence: 99%
“…Casp1 is an enzyme involved in the up-regulation of inflammation and apoptosis [25], while Lpar1 is a GPCR involved in developmental, physiologic and pathophysiologic processes, and has also been shown to activate PKB as well as Rho pathways [26]. In addition, Tnfsf14 and Tnfrsf1b both have been shown to play a role in the activation of NFκB and apoptosis [21], while Tlr6, through its interaction with Tlr2, is involved in the immune response [27]. Hence, it appears that PKB inhibition leads to an increase in the abundance of mRNAs arising from genes important for induction of apoptosis, suggesting a role for PKB in the inhibition of apoptosis following nuclear βAR stimulation.…”
Section: Targets Of β-Adrenergic Transcriptional Responses In Isolatementioning
confidence: 99%
“…17 Gram-positive bacteria are known to activate and mediate downstream signaling through heterodimerization of either TLR2/1 or TLR2/6. 18 Since TLR6 is downregulated in ulcers obtained from patients, C. pseudodiphtheriticum might initiate cell signaling via TLR2/1. However, the case is little different in immortalized cell lines, where both TLR1 and TLR6 is up-regulated and thus both TLR2/1 and TLR2/6 might be activated.…”
Section: Discussionmentioning
confidence: 99%